CHARTING THE UNSEEN: EXPLORING THE EFFECTS OF EPIGENETIC MODIFICATIONS ON SPERM AND THEIR ROLE IN MALE INFERTILITY - Al-Salihi, Abbas Abdul Wahhab Jumaah; Othman, Israa Sami; Saeed, Ban Thabit; AL-Saadi, Rana R. (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study aims to review existing literature on the impact of epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNA, on gene expression and their implications for human health and disease mechanisms. Methods: A literature review was conducted between January 2023 and October 2024, analyzing nine selected studies that explored the relationship between epigenetic mechanisms and gene expression in patients with various conditions, such as heart disease and cancer. Key methodologies discussed include RNA sequencing (RNA-Seq) for quantifying gene expression, chromatin immunoprecipitation sequencing (ChIP-Seq) for protein-DNA interaction analysis, and DNA microarray analysis for genome-wide gene expression profiling. Results: The findings highlight that DNA methylation suppresses gene expression by chemically modifying DNA, histone modifications alter chromatin structure to regulate gene accessibility, and non-coding RNAs influence transcription and translation processes. The interplay among these mechanisms was shown to regulate gene expression without requiring genetic mutations, resulting in diverse biological outcomes. The review also discusses the role of daily nutrition, potential complications, and therapeutic strategies targeting epigenetic modifications. Novelty: This study underscores the critical role of epigenetic changes in modulating gene expression and provides insights into their potential for advancing the understanding of disease mechanisms and developing novel approaches for diagnosis, treatment, and prevention.